Ventrolateral Periaqueductal Gray Neurons Are Active During Urination - Rao, Yu; Gao, Ziyan; Li, Xianping; Li, Xing; Li, Jun; Liang, Shanshan; Li, Daihan; Zhai, Jinliang; Yan, Junan; Yao, Jiwei; Chen, Xiaowei (Frontiers in Cellular Neuroscience, 2022)
The ventrolateral periaqueductal gray (VLPAG) is thought to be the main PAG column for bladder control. PAG neurons (especially VLPAG neurons) and neurons in the pontine micturition center (PMC) innervating the bladder detrusor have anatomical and functional synaptic connections. The prevailing viewpoint on neural control of the bladder is that PAG neurons receive information on the decision to void made by upstream brain regions, and consequently activate the PMC through their direct projections to initiate urination reﬂex. However, the exact location of the PMC-projecting VLPAG neurons, their activity in response to urination, and their whole-brain inputs remain unclear. Here, we identified the distribution of VLPAG neurons that may participate in control of the bladder or project to the PMC through retrograde neural tracing. Population Ca2+ signals of PMC-projecting VLPAG neurons highly correlated with bladder contractions and urination as shown by in vivo recording in freely moving animals. Using a RV-based retrograde trans-synaptic tracing strategy, morphological results showed that urination-related PMC-projecting VLPAG neurons received dense inputs from multiple urination-related higher brain areas, such as the medial preoptic area, medial prefrontal cortex, and lateral hypothalamus. Thus, our findings reveal a novel insight into the VLPAG for control of bladder function and provide a potential therapeutic midbrain node for neurogenic bladder dysfunction.